Development of a sustainable plant leather from the dried palm leaf sheaths of the Manila palm - Lazatin, Paola Francesca C.
The development of green materials to address the environmental effects of the textile industry can be attained through sustainable product design (SPD). The designer Tjeerd Veenhoven, for instance, developed a plant-based leather using the dried leaf sheaths of the abundant Areca palm in India as an alternative material to leather. Palms are also abundant in the Philippines but there have not been studies on the viability of using the palm leaf sheath as a textile material. Moreover, there have not been any attempts in applying decorative finishes on palms. This experimental study aimed to develop a plant leather using the endemic Manila Palm (MP) and apply different decorative finishes to it. To develop the MP, dried fallen leaf sheaths from the MP were collected and soaked in different solutions to soften the rigid leaf sheaths. It was found that soaking the MP in a 10% w/v NaOH solution for ten minutes then transferring the MP to a 25% v/v Glycerol solution for four days softened the sheaths. The developed MP plant leather sheet had low tensile strength and poor dimensional stability, which made it incomparable to leather. However, it had a high elongation which made it slightly akin to leather. Various decorative finishing techniques such as painting, embroidering, embellishing, laser cutting and engraving, molding, plaiting, fringing, appliqueing, and weaving were also proven to be applicable to the MP. The MP plant leather was found to be relatively sustainable as some of the raw materials used were renewable and non-toxic. The cost was also minimal, making it viable as a raw material for apparel, accessories and embellishments. However, the use of NaOH significantly reduced its sustainability. The researcher recommended to improve on the tensile strength and stability of the MP plant leather and to research on greener solutions to further improve the textile material.